2019
DOI: 10.3389/fnins.2019.00296
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane-Induced Burst Suppression Increases Intrinsic Functional Connectivity of the Monkey Brain

Abstract: Animal functional magnetic resonance imaging (fMRI) has provided key insights into the physiological mechanisms underlying healthy and diseased brain states. In non-human primates, resting-state fMRI studies are commonly conducted under isoflurane anesthesia, where anesthetic concentration is used to roughly infer anesthesia depth. However, within the recommended isoflurane concentration range (1.00–1.50%), the brain state can switch from moderate anesthesia characterized by stable slow wave (SW) electroenceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 56 publications
12
38
0
Order By: Relevance
“…The possibility to combine resting-state fMRI with invasive recordings of brain activity constitutes a pivotal branch of translational research (2018). Despite evidence of subtle changes in anesthesia level being able to dramatically change brain connectivity ( Grandjean et al, 2014 ; Hutchison et al, 2014 ; Zhang et al, 2019 ), little has been investigated on how the brain’s current state impacts functional connectivity derived from blood oxygenation level-dependent (BOLD) activity. While variations in functional connectivity have been related to cognitive state in humans ( Finn et al, 2017 ), the effect of neurophysiologically defined states on functional connectivity in the cortex remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to combine resting-state fMRI with invasive recordings of brain activity constitutes a pivotal branch of translational research (2018). Despite evidence of subtle changes in anesthesia level being able to dramatically change brain connectivity ( Grandjean et al, 2014 ; Hutchison et al, 2014 ; Zhang et al, 2019 ), little has been investigated on how the brain’s current state impacts functional connectivity derived from blood oxygenation level-dependent (BOLD) activity. While variations in functional connectivity have been related to cognitive state in humans ( Finn et al, 2017 ), the effect of neurophysiologically defined states on functional connectivity in the cortex remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to combine task-free fMRI with invasive recordings of brain activity constitutes a pivotal branch of translational research 39 . Surprisingly, in rodents as in humans, little has been investigated on how the brain's current state impacts functional connectivity derived from BOLD activity, despite evidence that, for instance, small changes in anesthesia can dramatically change brain connectivity 40,41 . While variations in functional connectivity have been related to cognitive state 42 in humans, the effect of neurophysiologically defined states on functional connectivity in the cortex remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Functional interactions between distributed brain areas within specific neural networks give rise to coherent patterns of hemodynamic signals, measured as BOLD activity. Covariant relations of spontaneous BOLD signals in the resting state have been reported in humans ( Arcaro et al, 2015a ; Biswal et al, 1995 ; Fox et al, 2009 ; Power et al, 2011 ; Sporns and Honey, 2013 ) and awake NHPs ( Belcher et al, 2016 ; Ghahremani et al, 2017 ; Hori et al, 2020a ; Leopold et al, 2003 ; Liu et al, 2013 ; Logothetis, 2003b ; Silva, 2017 ; Wang et al, 2012 ) as well as in anesthetized NHPs ( Hori et al, 2020a , b ; Hutchison et al, 2012 ; Hutchison et al, 2013 ; Mantini et al, 2012a ; Vincent et al, 2007 ; Wu et al, 2016 ; Wu et al, 2017 ; Zhang et al, 2019 ). These studies have revealed that specialized cognitive and sensory networks retain their basic functional connectivity, even when not specifically engaged in task-relevant operations.…”
Section: Non-invasive Imaging Methods Are Used In Experimental and CLmentioning
confidence: 89%
“…The volatile anesthetics isoflurane ( Hori et al, 2020a ; Hutchison et al, 2014 ; Li et al, 2013 ; Li et al, 2014 ; Li and Zhang, 2017 ; Vincent et al, 2007 ; Wu et al, 2016 ; Zhang et al, 2019 ) and sevoflurane ( Pró-Sistiaga et al, 2012 ; Uhrig et al, 2018 ) are attractive in that they can be safely administered to provide satisfactory depth of anesthesia, with relatively quick onset of action, and smooth recovery of the animals upon withdrawal of the anesthetic. Using ultra-high field MRI, it has been demonstrated that the T2*-oxygenation-ratio varied as a function of the anesthetic agent, showing a higher T2*-oxygenation-ratio under volatile anesthetics (isoflurane, sevoflurane) compared to intravenous anesthetics (propofol, ketamine, midazolam) ( Uhrig et al, 2014a ).…”
Section: Non-invasive Imaging Methods Are Used In Experimental and CLmentioning
confidence: 99%